Penerapan Sistem Pakar Untuk Mengidentifikasi Masalah Kehamilan Dengan Metode Dempster-Shafer - Ashari (LPPM Universitas Al Asyariah Mandar, 2015)
The study aims at creating an expert system application in identifying a pregnancy case. The data was analyzed by using Demster-Shafer based on resvonsive web. This data was obtained through : 1) Library Research; 2) Field Research; 3) Interview. This data is designed using the UML (Unifed Modeling Language). The result of the study indicated that the system can work well in accordance with the purpose. The expert system in identifying pregnancies case through web applications can give diagnosis, so it can help the pregnant women in doing diagnosis for a pregnancy problem.